2020
DOI: 10.1093/tas/txaa028
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and sex effects on digesta mean retention time in growing Saanen goats

Abstract: Despite the important role of digesta mean retention time (MRT) on digestive efficiency of ruminants, it is poorly investigated in total gastrointestinal tract (GIT) of growing ruminants, especially in goats. The objective of this study was to evaluate the effect of body weight (BW) and sex on GIT MRT of particles and solutes in growing Saanen goats. A dataset from two studies, comprising 103 individual records of castrated males (n = 36), females (n = 34), and intact males (n = 33) Saanen goats slaughtered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…When the variable sex was tested only for small ruminants fed ad libitum, it no longer influenced the prediction of GITwps. Similarly, Gindri et al [ 48 ] found that the sex did not affect GIT wet pool size or GIT wet tissue in growing goats. Furthermore, sex did not impact any of the model parameters for predicting the growth of GITwps in goats [ 59 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When the variable sex was tested only for small ruminants fed ad libitum, it no longer influenced the prediction of GITwps. Similarly, Gindri et al [ 48 ] found that the sex did not affect GIT wet pool size or GIT wet tissue in growing goats. Furthermore, sex did not impact any of the model parameters for predicting the growth of GITwps in goats [ 59 ].…”
Section: Discussionmentioning
confidence: 90%
“…This means that GITwps was proportional to BW, indicating that as the animals’ BW increased, the ratio of GIT pool size to BW decreased ( Figure 1 ). In a study by Gindri et al [ 48 ], a quadratic relationship was found between the total GITwps (g) and BW (kg) in Saanen goats weighing between 15 and 45 kg.…”
Section: Discussionmentioning
confidence: 99%